2012
DOI: 10.21091/mppa.2012.4036
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Disorders Among Iranian Instrumentalists

Abstract: Musicians as an occupational group are exposed to various ergonomic exposures which may lead to musculoskeletal problems. In this study we assessed the frequency of musculoskeletal disorders (MSDs) among Iranian instrumentalists (using traditional Iranian and western instruments). Methods: In a cross-sectional study we assessed the frequency of MSDs in 356 Iranian instrumentalists by standardized Nordic musculoskeletal questionnaire according to age group, type of instrument, duration of playing, and playing/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 0 publications
1
19
0
1
Order By: Relevance
“…Articles without a clear description of age of the study population, (Fjellman-Wiklund and Chesky 2006 ; Kreutz et al 2008 ; Hagglund and Jacobs 1996 ; Larsson et al 1993 ; Miller et al 2002 ; de Sousa et al 2014 ) and articles lacking a clearly described type of prevalence rate (Mishra et al 2013 ; Brandfonbrener 1997 ; Nemoto and Arino 2007 ; Mehrparvar et al 2012 ; Hagglund and Jacobs 1996 ; Marques et al 2003 ; Fjellman-Wiklund and Chesky 2006 ; Eller et al 1992 ; Caldron et al 1986 ; Wood 2014 ; Lopez and Farias 2013 ) were excluded. Also, studies with a mixed under aged population (Barton et al 2008 ; Zetterberg et al 1998 ; Caldron et al 1986 ; Shields and Dockrell 2000 ; Wood 2014 ) or mixed occupation (Arnason et al 2014 ; Wristen and Fountain 2013 ) (e.g., partly conductors or singers and not primary instrumental musicians) in which the authors were not able to present split data were excluded.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Articles without a clear description of age of the study population, (Fjellman-Wiklund and Chesky 2006 ; Kreutz et al 2008 ; Hagglund and Jacobs 1996 ; Larsson et al 1993 ; Miller et al 2002 ; de Sousa et al 2014 ) and articles lacking a clearly described type of prevalence rate (Mishra et al 2013 ; Brandfonbrener 1997 ; Nemoto and Arino 2007 ; Mehrparvar et al 2012 ; Hagglund and Jacobs 1996 ; Marques et al 2003 ; Fjellman-Wiklund and Chesky 2006 ; Eller et al 1992 ; Caldron et al 1986 ; Wood 2014 ; Lopez and Farias 2013 ) were excluded. Also, studies with a mixed under aged population (Barton et al 2008 ; Zetterberg et al 1998 ; Caldron et al 1986 ; Shields and Dockrell 2000 ; Wood 2014 ) or mixed occupation (Arnason et al 2014 ; Wristen and Fountain 2013 ) (e.g., partly conductors or singers and not primary instrumental musicians) in which the authors were not able to present split data were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, selection bias is often present in these studies. The latter is exemplified by missing general baseline information, like age and gender on the study subjects as well as which patients are selected to be included in the study and what the loss of follow-up is (i.e., response rate) (Eller et al 1992 ; Fjellman-Wiklund and Chesky 2006 ; Kreutz et al 2008 ; Hagglund and Jacobs 1996 ; Larsson et al 1993 ; Miller et al 2002 ; Brandfonbrener 1997 ; Nemoto and Arino 2007 ; Mehrparvar et al 2012 ; Marques et al 2003 ; Caldron et al 1986 ; Arnason et al 2014 ; de Sousa et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, the musicians themselves were asked about the presence of symptoms; however, Ackermann and Driscoll [175] surveyed parents of child instrumentalists only, while McKechnie and Jacobs [177] surveyed child pianists, their parents and piano teachers. Eight unique studies compared the prevalence of MSS and/or the consequences experienced by musicians with other groups, comparing especially the following: children playing the accordion with non-musical children [171], adult musicians with the general population [161], university music students with university medical [53][54][55] or health students [123] [154] also included 3 other instruments in a graph regarding prevalence, but these were not labeled. Some studies had "others" groups where the instruments were not specified.…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…Some 22 studies also investigated the association between different MSS outcomes. Similar to the extent/severity studies, the majority (86%) of the studies of risk factors reported general symptom outcomes[27,28,30,38,[40][41][42][43][44][45][46][47][48][49][50]53,54,60,64,65,69,71,74,76,[79][80][81][82][83][84][85][86][87][88][91][92][93][95][96][97][106][107][108]110,111,115,116,119,122,125,126,[129][130][131][133][134][135][138][139][140][141][142][154][155]…”
mentioning
confidence: 99%
“…the ones who are engaged in numerous hours of artistic (performing arts) activities during their everyday life. Professional artists (especially musicians) experience a variety of positions (sitting or standing) for prolonged time that may not be of ergonomic nature and may lead to musculoskeletal problems [15]. Regional muscle pain syndromes (particularly of the upper limb, upper trunk, and neck), peripheral nerve disorders (including thoracic outlet syndrome, ulnar neuropathy at the elbow, and carpal tunnel syndrome), and postural abnormalities (caused by increased muscle tension in the neck and shoulders, scoliosis, kyphosis, leg-length discrepancy, and lack of spinal mobility) are the most common neuromuscular and musculoskeletal problems of instrumental musicians [17,28].…”
Section: Introductionmentioning
confidence: 99%